Kajian Yuridis Kesaksian Palsu Dalam Pembuktian Tindak Pidana - Latupeirissa, Christi Marvel; Hehanussa, Deassy Jacomina Anthoneta; Latupeirissa, Julianus Edwin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Evidence is a very decisive factor for judges in making decisions. Witnesses are needed in explaining a case. In giving testimony, witnesses must provide truthful information. In order for witness testimony to be considered valid, it must meet the conditions specified in the Criminal Procedure Code. A statement given under oath where the content contradicts the truth both in a positive sense, namely giving false information (fabricating) or in a negative sense, namely hiding the truth, is also called perjury.Purposes of the Research: to analyze explaining that false testimony is a crime as well as the mechanism for handling or legal remedies against false testimony in proving a crime.Methods of the Research: The type of research used in this study is normative juridical. The sources of legal materials are primary and secondary legal materials. Data collection techniques are carried out through identification of laws and regulations, legal journals, books.Results of the Research: the construction of false testimony in the Criminal Code must fulfill the element of testimony that must be under oath. The statement must be required by law or according to regulations that determine the legal consequences of said statement, the statement must be false (incorrect) and this falsehood is known to the giver of the statement. Second, proving the act of justifying false testimony in criminal procedural law can be carried out if the witness continues to defend his statement until the witness examination is complete, then a criminal act of perjury occurs which is then supported by a decision stating that the defendant has not been legally and convincingly proven and the judge orders the defendant to immediately released from custody so that this will become the subject of a new case that can be reported by the defendant's lawyer or the defendant himself